2018
DOI: 10.14710/jaa.15.1.91-114
|View full text |Cite
|
Sign up to set email alerts
|

Individual Characteristics, Financial Literacy and Ability in Detecting Investment Scams

Abstract: This study aims to explore important indicators applicable for the early detection of investment scams and to investigate the effect of age, education and financial literacy on the ability to detectinvestment scams. Data were collected using a questionnaire survey with respondents inSemarang, Indonesia. A total of 311 respondents completed the questionnaires, for a 62.2%response rate, but only 304 questionnaires were usable. Confirmatory factor analysis was used toverify the indicators of investment scams, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Besides Greenspan (2009), Manning (2018) also found that victims tend to be those of limited financial knowledge. This is consistent with Chariri, Sektiyani, Nurlina and Wulandari (2018) which noted that the level of individual financial literacy positively affects the ability to detect investment scams. Lokanan (2014) added that some victims joined because they are poor and desperate to make ends meet.…”
Section: Characteristics and Modus Operandisupporting
confidence: 90%
“…Besides Greenspan (2009), Manning (2018) also found that victims tend to be those of limited financial knowledge. This is consistent with Chariri, Sektiyani, Nurlina and Wulandari (2018) which noted that the level of individual financial literacy positively affects the ability to detect investment scams. Lokanan (2014) added that some victims joined because they are poor and desperate to make ends meet.…”
Section: Characteristics and Modus Operandisupporting
confidence: 90%
“…Although fraud is prevalent in all facets of the finance and investment industry, the hedge fund industry is infamous for fraud that has occurred (Baucus & Mitteness, 2016; Phillips, 2004). Many cases of hedge fund indiscretions, including those observed in the Madoff Ponzi scheme were because of fund managers having the ability to both misreport fund values as well to completely fabricate returns (Bollen & Pool, 2012; Chariri et al, 2018). This ability possessed by hedge fund managers is due to the environment in which hedge funds operate where there is little regulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also the ability of individuals to evaluate. Financial literacy is an important component of investment activities, so one can avoid investment fraud [13].Most studies on financial literacy are the knowledge of adults or students and aims to explore capabilities. As a result, questions Usually refer to their living environment, and their consumers Discuss investment behavior about education or changes in investment behavior caused by the financial crisis.…”
Section: Financial Literacymentioning
confidence: 99%